Pengaruh Etika Terhadap Kepercayaan Konsumen Dalam Iklan - Ikhwan Nur Hakim; Muhammad Diva Fadhila; Muktamar Zaky; Daniel Handoko (STIKes Ibnu Sina Ajibarang, 2024)
The abstract in English: This study investigates the impact of ethics on consumer trust in advertising. The research examines how ethical considerations in advertisements influence consumer perceptions and trust. The study uses a mixed-methods approach to analyze data collected from surveys and interviews. The findings reveal that ethical advertising significantly enhances consumer trust, leading to greater brand loyalty and positive word-of-mouth. These implications highlight the importance of maintaining high ethical standards in advertising practices.